2020
DOI: 10.1016/j.cemconcomp.2020.103760
|View full text |Cite
|
Sign up to set email alerts
|

Drying shrinkage, strength and microstructure of alkali-activated high-calcium fly ash using FGD-gypsum and dolomite as expansive additive

Abstract: This paper aims to investigate drying shrinkage, strength development, and microstructure of alkali-activated high-calcium fly ash (AAFA) paste by using FGD-gypsum 2 (FGD) and dolomite (DLM) as the expansive additive. The 10 molar of sodium hydroxide combined with sodium silicate solutions were used as liquid alkaline activation in all mixtures. The preparation of the AAFA paste was divided into 2 steps. First, the study was focused on the effects of expansive additive (FGD and DLM) and liquid/binder (L/B) rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 63 publications
1
9
0
1
Order By: Relevance
“…Cementitious materials are widely accepted for passive fire protection because of their cost effectiveness, low thermal conductivity, and non-combustibility. Cementitious materials are also compatible and work well with different kinds of property enhancement additives or materials on both micro- and macro-structure levels, for example, carbon nanotube [ 6 , 12 ], graphene oxide [ 13 , 14 , 15 ], polymeric materials [ 16 , 17 , 18 , 19 ], phase change materials [ 20 , 21 , 22 , 23 ], fibers [ 24 , 25 , 26 , 27 , 28 , 29 ], mineral materials [ 30 , 31 , 32 ], crumb rubber [ 33 , 34 , 35 ], etc. Especially in the case of polymeric material such as superabsorbent polymer (SP), during the past decade there has been a growing interest in the application of SPs in cement-based materials [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cementitious materials are widely accepted for passive fire protection because of their cost effectiveness, low thermal conductivity, and non-combustibility. Cementitious materials are also compatible and work well with different kinds of property enhancement additives or materials on both micro- and macro-structure levels, for example, carbon nanotube [ 6 , 12 ], graphene oxide [ 13 , 14 , 15 ], polymeric materials [ 16 , 17 , 18 , 19 ], phase change materials [ 20 , 21 , 22 , 23 ], fibers [ 24 , 25 , 26 , 27 , 28 , 29 ], mineral materials [ 30 , 31 , 32 ], crumb rubber [ 33 , 34 , 35 ], etc. Especially in the case of polymeric material such as superabsorbent polymer (SP), during the past decade there has been a growing interest in the application of SPs in cement-based materials [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the formation of hydration products (AFt and CH) could reduce the drying shrinkage. Other studies [37,43,44] also found that the compensation effect on shrinkage was carried out due to the formation of AFt and AFm.…”
Section: Introductionmentioning
confidence: 84%
“…Without any treatment, the GP and LP are utilized as additions to prepare the backfill paste. The GP (expressed as CaSO 4 ·2H 2 O) has slight expansion properties [ 40 ], with 30.5% CaO and 40.6% SO 3 by mass. Because of the high CaO content (71.2% by mass), the LP has high water absorption and hydration reactivity.…”
Section: Methodsmentioning
confidence: 99%